Systematic Literature Review on Troubleshooting Delivery of Production Product Using n-Vehicle with Vogel Total Difference Approach Method - Al Fataa Waliyyul Haq; Sudradjat Supian; Diah Chaerani (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The product delivery strategy using n-vehicle is the application of optimization for transportation problems. The product delivery strategy using n-vehicle is useful for minimizing the shipping costs of a company’s production. This article presents a peer-reviewed bibliometric analysis based on the topic of production delivery strategies using n-vehicle. Overall, there are 91 articles from the Dimension, Science Direct, and Google Scholar databases in 2013-2021 that use the topic of production delivery strategies using n-vehicle based on the keywords ”Capacitated transportation problem” and ”cost” and ”vehicle” and” optimal solutions”. The researcher presents the relationship of each cited article so that it can show the collaboration of all the cited articles. This article aims to generate and review analysis results through Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and State of The Art. Bibliometric analysis, PRISMA, and State of The Art show how the development of research on production delivery strategies using n-vehicle. So, it can produce suggestions in conducting the latest research related to studies on the topic of production delivery strategies using n-vehicle. Based on PRISMA’s analysis, 91 articles were obtained, of those 91 articles, 11 articles discussed the strategy of delivering production products using n-vehicle in depth. The State of The Art also shows how the development of research on production delivery strategies using n-vehicle is developing. It can be seen that apart from the classical method, other methods are also emerging to solve transportation problems. One of them is Vogel Total Difference Approach Method (VTDM).